2013
DOI: 10.1111/jgh.12263
|View full text |Cite
|
Sign up to set email alerts
|

Addition of thiopurines can recapture response in patients with Crohn's disease who have lost response to anti‐tumor necrosis factor monotherapy

Abstract: Addition of a thiopurine in patients who have lost response to anti-TNF monotherapy is an effective strategy to recapture response even if the patient has previously failed thiopurine therapy. Thiopurines may reduce immunogenicity or act synergistically with anti-TNF therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…In addition, it has recently been published that thiopurine – infliximab cotherapy in Crohn's disease patients is associated with reduced antibody formation, regardless of initial thiopurine therapeutic effect . Recapture of clinical response upon addition of an immunomodulator has also been reported among adalimumab therapy patients, who had previously failed immunomodulators, although immunogenicity and drug levels have not been evaluated in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has recently been published that thiopurine – infliximab cotherapy in Crohn's disease patients is associated with reduced antibody formation, regardless of initial thiopurine therapeutic effect . Recapture of clinical response upon addition of an immunomodulator has also been reported among adalimumab therapy patients, who had previously failed immunomodulators, although immunogenicity and drug levels have not been evaluated in these reports.…”
Section: Discussionmentioning
confidence: 99%
“…164 165 However, infliximab rescue therapy may be even less efficacious in hospital inpatients with more severe, steroid refractory disease, with 90 day colectomy rates reported as 29-60%. [155][156][157][158][159][160][161][162][163][164][165][166][167][168] A cohort study of 115 patients found that standard three dose infliximab induction was associated with lower rates of clinical response (70% v 41%; P=0.004), clinical remission (41% v 17%; P=0.015), and endoscopic remission (26% v 4%; P=0.046) in patients with severe ulcerative colitis than in those with only moderately severe disease. 155 Similarly, patients with severe ulcerative colitis who did not respond to infliximab induction had significantly more fecal loss of drug, 169 and lower day 14 trough levels 170 compared with infliximab responders.…”
Section: Skin Lesionsmentioning
confidence: 99%
“…Similarly to infliximab, additional pharmacokinetic studies showed that antibodies to adalimumab predicted Crohn's disease recurrence [52]. As well, adding an immunomodulator for combination therapy may recapture response to adalimumab [53]. With multiple approved and available antiTNFa antibodies, it is common that patients will have treatment with several agents within the class.…”
Section: Currently Available Therapeutic Antibodies In Digestive Disementioning
confidence: 99%